Eutrombicula tinami (Oudemans, 1910) (Trombidiformes: Trombiculidae) in Brazil: A neglected ectoparasite of several animals including humans - Bassini-Silva, Ricardo; Jacinavicius, Fernando de Castro; Pinter, Adriano; Fournier, Gislene F. S. R.; Lugarini, Camile; Ferreira, Ariane; Moreira-Lima, Luciano; Hingst-Zaher, Erika; Welbourn, Cal; Ochoa, Ron; Barros-Battesti, Darci Moraes [UNESP] (Les Amis d'Acarologia, 2019)
The genus Eutrombicula comprises ca. 80 species worldwide, some of which have been reported as causative agents of severe irritation to the host’s skin, known as trombiculiasis. Six species of Eutrombicula have been recorded from Brazil until present, with two reports of humans as hosts. In this study, Eutrombicula tinami (Oudemans) is redescribed and new records for the states of Minas Gerais, Rio de Janeiro, Santa Catarina and São Paulo as well as new parasite-host associations with Columbiformes, Cuculiformes, Passeriformes, Tinamiformes, Carnivora, Didelphimorphia and Lagomorpha are listed. Besides that, a two detailed report cases of trombiculiasis is provided.
Keywords: Birds; Chiggers; Distribution; Ectoparasites; Hosts; Mammals; Trombiculiasis